Axonemal localization of the dynein component DNAH5 is not altered in secondary ciliary dyskinesia - Olbrich, Heike; Sautermeister, Judit; Fekete, Andrea; Loges, Niki Tomas; Stormvan's Gravesande, Karin; Blum, Andreas; Hörmann, Karl; Omran, Heymut (Pediatric research, 2006)
Primary ciliary dyskinesia (PCD) is a heterogeneous genetic disorder characterized by recurrent airway infections and situs inversus in half of affected individuals. Diagnosis currently relies on demonstration of abnormal ciliary ultrastructure or altered ciliary beat. Alterations encountered in secondary ciliary dyskinesia (SCD) caused by inflammation often complicate the diagnostic workup. We have recently shown that in respiratory epithelial cells from PCD patients with outer dynein arm defects the dynein protein DNAH5 is mislocalized and either completely or partially absent from the ciliary axoneme. In this study, we addressed the question whether SCD might affect axonemal DNAH5 localization in respiratory cells. To induce SCD in vitro, we treated primary human respiratory epithelial cell cultures with interleukin-13 (IL-13). Ciliary function and ultrastructure were assessed by high-speed videomicroscopy and transmission electron microscopy, respectively. For in vivo localization of DNAH5, we performed nasal brushing biopsies in patients with evidence of SCD. Expression of DNAH5 was analyzed by immunofluorescence microscopy. IL-13-treated cells showed evidence of SCD. Ciliary beat frequency was significantly reduced and ultrastructural analyses showed axonemal disorganization compared with control cells. High-resolution immunofluorescence studies of respiratory epithelial cells with SCD identified in vitro and in vivo normal axonemal DNAH5 localization. DNAH5 localization is not altered by SCD, indicating a high potential for immunofluorescence analysis as a novel diagnostic tool in PCD.
Gesehen am 11.03.2022